Used of Growth Charts among Children Age 1-5 Years Old and its Effects on Child Health in Al-Hillah City - Amean A. Yasir (Journal of Global Pharma Technology, 2017)
Depending on the height, weight and head circumstances derived from 400 children (200 boys and 200 girls) ranged from one to five years of age. The data collected randomly from different health care centre of Hillah. The result showed that boys were significantly heavier and taller than girls in the first years of life. Height measurement revealed that boys head are bigger than the girls. Objective this study aimed to suggested new technique of physical growth curve chart for children under five years old of age in non-probability sample.Keywords: Physical Growth charts, Child health, WHO, CDC, Weight, Height and head circumference.